TJNPR 2021
DOI: 10.26538/tjnpr/v5i1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Participation of Healthcare Insurance and Social Security (BPJS) on Therapeutic Success in Diabetes Mellitus Patients at Primary Healthcare Centers in Madura

Abstract: In 2013, East Java was the province with the fifth highest DM prevelence in Indonesia. 3 The increase in the prevalence of diabetes mellitus is followed by an increase in complication with varying conditions, including physical, psychological, social, and economic complications. Physical complications that occur include eye damage, kidney damage, heart disease, high blood pressure, stroke, 4 and gangrene. Diabetes can also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…This study found that, as indicated in Table I, even though the respondents did routine check-ups, they poorly adhere to medication. Similarly, Rahem et al also found in their study that many patients did not comply with medication for various reasons (Rahem, Athiyah & Setiawan, 2021).…”
Section: Discussionmentioning
confidence: 68%
“…This study found that, as indicated in Table I, even though the respondents did routine check-ups, they poorly adhere to medication. Similarly, Rahem et al also found in their study that many patients did not comply with medication for various reasons (Rahem, Athiyah & Setiawan, 2021).…”
Section: Discussionmentioning
confidence: 68%
“…Dalam hal menjadi peserta BPJS pemberi kerja harusnya secara bertahap mendaftarkan dirinya dan pekerjanya yang berpedoman pada program jaminan sosial (Athiyah, 2019;Rahem, 2021;Saleh, 2020)yang akan di ikuti karena apabila dengan sengaja pemberi kerja tidak mendaftarkan pekerjanya pada BPJS sesuai dengan Peraturan Pemerintah Nomor 14 Tahun 1993 tentang Penyelenggara Program Jaminan Sosial Tenaga Kerja dengan perubahan terakhir menjadi Peraturan Pemerintah No 84 Tahun 2013, pemberi kerja dikenakan sanksi administrative (Agusmidah, 2010;Khoe, 2020;Lampe, 2020;Saleh, 2020).…”
Section: Pendahuluanunclassified